Root phenotyping of soybean (Glycine Max (L.) Merr.)related to nodulation and biological nitrogen fixation - Vorster, Barend Juan (University of Pretoria, 2022)
Dissertation (MSc Agric (Agronomy))--University of Pretoria, 2021